Metabolism-driven and high-efficiency mining of ethanol-tolerant microorganisms from pit mud microbiota using Raman-activated cell sorting - Teng Xu; Qing Sun; Gongchao Jing; Yongming Duan; Xiaohang Wang; Xinyun Yi; Changle Wu; Huizi Zhu; Bo Ma; Jian Xu; Xiaowei Zheng; Xixian Wang; et al. (Bioresource Technology, 2026)

Polystyrene microplastic exposure induces hepatic damage via immune-modulated autophagy and ferroptosis in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Xiaolong Fan; Xiaomeng Guo; Na Guo; Tian Gao; Changle Zhao; Yuanyuan Li; Haiyan Xu; Fan Bai; Yixin Chen; Deshou Wang; Lina Sun; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Mechanisms of water-inrush mitigation under alternative grouting strategies during shaft sinking: Solidification-enabled stress–seepage–damage coupling - Wenxin Li; Dan Ma; Jiangyu Wu; Xuefeng Gao; Qiang Li; Changle Xu; Chuanjiu Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Effects of Dietary Choline on Endogenous Phospholipid Synthesis in Juvenile Chinese Mitten Crab (Eriocheir sinensis) - Yang Xu; Mengyu Shi; Ping Wu; Yuanqin Zhang; Samwel Mchele Limbu; Jinyun Ye; Changle Qi (Fishes, 2026)
This study investigated the effects of choline on endogenous phospholipid synthesis in Chinese mitten crab (Eriocheir sinensis). Chinese mitten crabs (0.40 ± 0.03 g) were fed diets supplemented with 0%, 0.2% or 0.4% choline under low phospholipids (low-PL) or normal phospholipids (normal-PL) for eight weeks. The results showed that feeding the Chinese mitten crab with 0.4% choline in low-PL diets up-regulated significantly the relative mRNA expressions of neuropathy target enzyme 1 (nte1), phospholipase A2 (pla2) and phospholipase B (plb). Moreover, the crabs fed the 0.4% diet at low-PL diets enhanced hepatopancreatic fatty acid binding protein 3 (fabp3), fatty acid transporter protein 4 (fatp4), carnitine palmitoyltransferase-2 (cpt-2), carnitine acetyltransferase (caat), carnitine palmitoyltransferase-1a (cpt-1a) and carnitine palmitoyltransferase-1b (cpt-1b). However, feeding the mitten crabs 0.2% choline in the normal-PL diets diets up-regulated significantly the relative mRNA expressions of nte1, pla2 and plb. These results indicate that 0.4% choline up-regulates the expressions of genes involving in phospholipids synthesis of Chinese mitten crab fed with low-PL diets, while 0.2% choline improved the genes involved in phospholipid decomposition under normal-PL conditions.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Time-dependent biphasic dysregulation of autophagy and innate immunity underlies polystyrene microplastics-induced hepatotoxicity in Nile tilapia - Feilong Wang; Xiaomeng Guo; Na Guo; Xiaolong Fan; Haiyan Xu; Yuanyuan Li; Tian Gao; Yixin Chen; Changle Zhao; Lina Sun; Deshou Wang; Xin Xie; et al. (Aquatic Toxicology, 2026)

Efficient and Intelligent Positioning of Potentially Unstable Rock Masses in Rock Slope Engineering: Case Study from a Hydropower Station in Southwest China - Yongqiang Liu; Da Huang; Jiewei Zhan; Changle Pu; Zhaowei Yao; Seyedahmad Mehrishal; Jae Joon Song; Zhanglei Wu (Rock Mechanics and Rock Engineering, 2026)

High-entropy metal hexacyanoferrate for excellent capacitive deionization - Changle Li; Binbin Tao; Wenjie Wu; Manal S. Ebaid; Eman A. Ayob; Kaidan Zheng; Zeinhom M. El-Bahy; Xingtao Xu; Yusuke Yamauchi; Jiabao Li (Desalination, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Hepatic cyp24a1 serves as a biomarker for diagnosing polystyrene microplastic exposure in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Haiyan Xu; Xiaomeng Guo; Xiaolong Fan; Yuanyuan Li; Tiao Gao; Xin Xie; Na Guo; Fan Bai; Yixin Chen; Changle Zhao; Deshou Wang; et al. (Aquatic Toxicology, 2026)

Interpretation and Characterization of Sedimentary Rock Mass Structure Using UAV Multi-Sensor Data - Changle Pu; Jiewei Zhan; Da Huang; Wu Zhu; Jianbing Peng (Rock Mechanics and Rock Engineering, 2025)

Codon usage pattern and genetic diversity in chloroplast genomes of Zanthoxylum species (Sapindales: Rutaceae) - Changle Li; Songping Wu; Jiangbo Nie; Ling Zhou; Yonghong Liu; Yulin Liu (Acta Physiologiae Plantarum, 2025)

Five new chromane meroditerpenoids from the brown alga Sargassum siliquastrum of China Sea - Junzhi Pan; Huayuan Liu; Junpeng Xu; Xiaofeng Xu; Yu Qi; Chaojie Wang; Changle Wu; Zhongmin Sun; Yali Lv; Pengcheng Yan (Phytochemistry Letters, 2024)

Codon usage bias and genetic diversity in chloroplast genomes of Elaeagnus species (Myrtiflorae: Elaeagnaceae) - Changle Li; Ling Zhou; Jiangbo Nie; Songping Wu; Wei Li; Yonghong Liu; Yulin Liu (Physiology and Molecular Biology of Plants, 2023)

LncRNA NONRATT021972 siRNA attenuates P2X7 receptor expression and inflammatory cytokine production induced by combined high glucose and free fatty acids in PC12 cells - Hong Xu; Luling He; Changle Liu; Lan Tang; Yonghu Xu; Mengqi Xiong; Mei Yang; Yongfang Fan; Fangfang Hu; Xingzi Liu; Lu Ding; Yun Gao; et al. (Purinergic Signalling, 2016)

Association of CDKN1B gene polymorphisms with susceptibility to breast cancer: a meta-analysis - Heping Xiang; He Li; Weiwei Ge; Weidong Wu; Ming Gao; Wei Wang; Lei Hong; Datong Jiang; Changle Zhang (Molecular Biology Reports, 2013)